Prognostic analysis and association of the systemic immune-inflammatory index with immune checkpoint inhibitor pneumonitis in patients with non-small cell lung cancer - Cai, Mengyao; Sun, Jiangqian; Wu, Jingyi; Liu, Ya; Huang, Yuanyi (Frontiers in Oncology, 2025)
ObjectiveThe Systemic Immune-Inflammatory Index (SII) is a comprehensive indicator reflecting immune response and disease burden. However, its significance in immune checkpoint inhibitor-related pneumonitis (CIP) in cases of non-small cell lung cancer (NSCLC) remains poorly explored. This study evaluated the association between SII and the incidence, severity, and prognostic effects of CIP in NSCLC patients.MethodsA retrospective analysis involved 215 NSCLC patients receiving immune checkpoint inhibitor (ICI) therapy, of whom 35 developed CIP while 180 did not. Baseline clinical characteristics and dynamic changes in peripheral blood biochemical markers were analyzed. Risk factors associated with the onset and severity of CIP were assessed, along with the diagnostic application of the SII for CIP.ResultsMultivariate logistic regression identified smoking history (odds ratio [OR]: 3.23; p = 0.01), pre-existing lung disease (OR: 3.36; p < 0.01), squamous cell carcinoma (OR: 2.39; p = 0.03), and combined ICI therapy (OR: 4.77; p < 0.01) as independent risk factors for CIP onset. SII was also identified as independently predictive of severe CIP (OR: 6.35; p = 0.04). Receiver operating characteristic (ROC) curves demonstrated that SII had moderate accuracy for diagnosing CIP (area under the curve [AUC]: 0.63) and high diagnostic accuracy for severe CIP (AUC: 0.81). Multivariate Cox regression also showed that severe CIP was substantially related to reduced overall survival (OS) relative to mild CIP (hazard ratio [HR]: 0.06, 95% confidence interval [CI]: 0.01–0.52; p = 0.01).ConclusionThe results suggested the potential of SII as an indicator for diagnosing the presence and severity of CIP. Elevated SII levels were independently associated with the development of severe CIP, which, in turn, emerged as a key prognostic factor influencing overall survival in affected patients.